2021
DOI: 10.21608/fjard.2021.222930
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of direct and indirect methods used to determine crop coefficient and crop evapotranspiration of sugar beet plants grown under fayoum conditions

Abstract: With increasing water scarcity, the determination of reference evapotranspiration ETo and crop coefficient (Kc) is a critical factor in determining the crop water demand ETc. Therefore, the current investigation aimed to evaluate and compare the estimated sugar beet crop evapotranspiration (ETc) values computed by different empirical methods (e.g. Hargreaves, Penmen-Monteith and Class-A pan) with the measured actual sugar beet evapotranspiration (ETa). To determine the ETa for sugar beet crop field experiment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
1
0
0
Order By: Relevance
“…The results also, indicated that the ETp value higher in the first season than that of the second one. The fluctuation in the ETp values indicated by growing periods it could be contributed to the changes in climate conditions during the whole growth period of sugarbeet, similar results were obtained byOsman et al (2005) andEl-Samnoudi et al (2021).…”
supporting
confidence: 86%
“…The results also, indicated that the ETp value higher in the first season than that of the second one. The fluctuation in the ETp values indicated by growing periods it could be contributed to the changes in climate conditions during the whole growth period of sugarbeet, similar results were obtained byOsman et al (2005) andEl-Samnoudi et al (2021).…”
supporting
confidence: 86%